The Impact of Social Media Marketing on Brand Equity toward the Purchase Intention of Starbucks Indonesia - Melissa Anastasia Karman (iBuss Management, 2015)
Starbucks Indonesia is a global coffee company has been able to manage its strong presence in the retail coffee industry. However, the burgeoning independent coffee shops in several major cities of Indonesia has become  the new competitor for Starbucks Indonesia. This research is aimed to analyze the impact of social media marketing on brand equity toward the purchase intention of Starbucks Indonesia. Moreover, this research attempts to examine the role of brand equity as  the mediating variable of social media marketing and customer purchase intention.There are 122 respondents gathered in this research from the simple random sampling. This research used reliability and validity test and classical assumption tests as data-processing method. Then, path analysis with linear regression, and Sobel test to prove the mediation effect were used for the data-analysis. This research’s findings indicate that social media marketing has significant impact toward the purchase intention  of Starbucks Indonesia. In addition, online communities, interaction, and sharing of content were found to have significant impact toward the purchase intention of Starbucks Indonesia. Brand equity is also found to be the mediating variable between social media marketing and purchase intention of Starbucks Indonesia.Keywords: Social Media Marketing, Brand Equity, and Purchase Intention.